Legends of Zita the spacegirl - Hatke, Ben (First Second, 2012)
Zita is determined to find her way home to Earth, but her exploits have made her an intergalactic megastar, and as her true self is eclipsed by her public persona, she faces a robot doppelganger, unsure of who she can trust.